Interpreting negative test results when assessing cancer risk in general practice - Bradley, SH; Nicholson, BD; Funston, G (Royal College of General Practitioners, 2021)
Studies published over the last year have established the sensitivity of chest X-ray (CXR) for lung cancer (75%, 95% confidence interval [CI] = 68 to 83), cancer antigen 125 (CA125) for ovarian cancer (77%, 95% CI = 73 to 81), and the faecal immunochemical test (FIT) for colorectal cancer (91%, 95% CI = 85 to 96) in symptomatic people attending primary care.1–3 This research demonstrates how simple and accessible tests can be used by GPs to identify these cancers in most cases; however, it also raises questions about how GPs should respond to negative test results in situations in which there is some concern about the possibility for cancer, but criteria for an urgent suspected cancer referral are not met.